The Impact of Political Relations on China’s Outward Direct Investment - Lin Zhang; Xiaoqiong Hao (Entrepreneurial Business and Economics Review)
Objective: This article relates to the growing amount of literature on the determinants of the location choice of Chinese ODI. The objective of the article is to investigate whether the improvement in political relations will encourage more investment to a host country or not. Also, the article aims to identify the asymmetric impact of political relations in different host countries.